Faith in the Enlightenment? : the critique of the enlightenment revisited - Boeve, Lieven (Amsterdam ; New York : Rodopi, 2006)
One of the urgent tasks of modern philosophy is to find a path between the rationalism of the Enlightenment and the relativism of postmodernism. Rationalism alone cannot suffice to solve today's problems, but neither can we dispense with reasonable critique. The task is to find ways to broaden the scope of rational thought without losing its critical power. The first part of this volume explores the ideas of Enlightenment philosophers and shows nuances often absent from the common view of the Enlightenment. The second part deals with some of the modern heirs of Enlightenment, such as Durkheim, Habermas, and Derrida. In the third part this volume looks at alternatives to Enlightenment thought in West European, Russian and Buddhist philosophy. Part four provides, over against the Enlightenment, a new starting point for the philosophy of religion in thinking about human beings, God, and the description of phenomena.
INTRODUCTION: Enlightenment in Discussion; PART I: HIGHPOINTS OF THE ENLIGHTENMENT; PART II: THE CONTINUATION OF THE PROJECT OF THE ENLIGHTENMENT?; PART III: ALTERNATIVES TO THE ENLIGHTENMENT; PART IV: A NEW APPROACH; List of Contributors; Index of Names; Index of Subjects.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Enlightenment -- History; Enlightenment -- Religious aspects; Siècle des Lumières -- Histoire; Siècle des Lumières -- Aspect religieux; PHILOSOPHY -- History & Surveys -- Modern; Enlightenment; Aufklärung; Religion; Cultuurfilosofie; Verlichting (cultuurgeschiedenis); Foi; Doute; Croyance (théorie de la connaissance); Mouvement des Lumières.; Raison; History